Chapter António Correia e a sua sede de escrita, na ânsia de revelar uma nova humanidade ao mundo - Matos, Ernesto (Studi di Traduzione Letteraria Lusofona, 2023)
The personal memory of Ernesto Matos focuses on the friendship with António Correia, together with their passion for writing and the stones of the city of Macau as a new symbolic way to observe the world and its humanity